A Letter About Phenobarbital Poisoning - Ataee, Zahra; Sayyari Doughabadi, Maryam (International Journal of Medical Toxicology and Forensic Medicine, 2020)
The ever-increasing sensitivity of humans and living in a world full of stress and anxiety have led to the increased consumption of painkillers and sleeping pills. Barbiturates, which are among the most important sedatives, are regularly used by ordinary people. Addiction, suicide, and accidental deaths from inappropriate use of these drugs have been a subject of constant concern in medicine.